2023
DOI: 10.21203/rs.3.rs-3241262/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Study on the difference of physical activities and static activities between urban and rural elderly and its influencing factors - Empirical Analysis Based on 2018 CLHLS Data

Keying Song,
Zijian zhao

Abstract: Using the data of CLHLS in 2018, the differences of physical activities, static activities and influencing factors between urban and rural elderly in China were studied.The results showed that there were still significant differences in physical activities and static activities between urban and rural elderly in China (p<0.001) and the proportion of urban and rural elderly people participating in static activities is significantly higher than the proportion of physical exercise (61.62% vs 34.91%, 51.52% vs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Accordingly, policy implications on how to sustain and promote the existing positive impact of FDI inflows on China's economy are proposed [3] . Based on the time series data from 2000-2015, Song Yingying (2017 did an empirical analysis of the economic growth effect of FDI using the Cobb Douglas production function model and showed that there is a long-term stable relationship between FDI inflows and GDP growth, and based on the findings also proposed countermeasures on how to better use FDI to promote economic development [4] . Liu Wenyong et al ( 2006) also construct a model based on the Cobb Douglas production function and argue the impact of FDI on China's economic development, and draw analytical conclusions from several aspects such as capital-economic growth effect, employment-economic growth effect, employment effect, export effect, and technological progress effect, and argue that FDI has both contributed to China's economic growth and posed certain threats, thus giving policy recommendations [5] .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Accordingly, policy implications on how to sustain and promote the existing positive impact of FDI inflows on China's economy are proposed [3] . Based on the time series data from 2000-2015, Song Yingying (2017 did an empirical analysis of the economic growth effect of FDI using the Cobb Douglas production function model and showed that there is a long-term stable relationship between FDI inflows and GDP growth, and based on the findings also proposed countermeasures on how to better use FDI to promote economic development [4] . Liu Wenyong et al ( 2006) also construct a model based on the Cobb Douglas production function and argue the impact of FDI on China's economic development, and draw analytical conclusions from several aspects such as capital-economic growth effect, employment-economic growth effect, employment effect, export effect, and technological progress effect, and argue that FDI has both contributed to China's economic growth and posed certain threats, thus giving policy recommendations [5] .…”
Section: Literature Reviewmentioning
confidence: 99%